(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research aims to investigate how young customers’ perceptions of brands influence their buying behavior of fast-moving consumer goods (FMCG). The data was collected using a convenience sample strategy, which included employing the interview schedule. We chose 185 responders at random. The researcher in this study used straightforward regression and percentage analysis. According to the results, those who are more self-conscious about their social standing tend to buy branded fast-moving consumer goods. Insights into these beliefs provide a foundation for future research into the factors influencing young people’s decisions and actions in the fast-paced fast-moving consumer goods (FMCG) industry. The results have important ramifications for politicians, corporations, and marketers who are trying to meet the changing demands of this important demographic of consumers.